STUDI PERBANDINGAN MOTIVASI BELAJAR ONLINE ANTARA SISWA LAKI-LAKI DAN PEREMPUAN PADA MATA PELAJARAN PPKN DI SMAN 1 KARIMUN - Annisa Azzhara; Gimin Gimin; Separen Separen (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was motivated by the outbreak of pandemic cases caused by the Corona virus in Indonesia which resulted in learning activities that were usually carried out in schools now being carried out online from home. This research examines the comparison of learning motivation online between male and female students in civic education lessons at public Senior High School 1 Karimun. The formulation of the problem in this research is